(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The problem of human capital development in postindustrial Kazakhstan society is discussed in this article. Development of the human capital, in particular, development of the cultural capital, modernization of the country by development of intellectual potential of society is very important for progressive development of the Kazakhstan society. Value of the human capital in the conditions of globalization of world economy and a modern level of development of a civilization as factor of social and economic development steadily increases. One of decisive conditions of creation of post-industrial society in Kazakhstan is development of intellectual potential of the nation, reforming of an education system, modernization of culture and spiritual and moral values. Key words: human capital, cultural capital, the spiritual capital of the country modernization